Peningkatan Prestasi Belajar Materi Bilangan Berpangkat Melalui Model Discovery Learning - Mujiyanto Mujiyanto (Manajemen Pendidikan, 2016)
This research is motivated by the unoptimally the mastery of the material is still not optimal exponential number among learners and implementation Discovery learning in mathematic learning material on the exponential number of learners class IX A State of Junior High School One Cawas Klaten second semester of academic year 2014/2015. This study aimed to describe the optimization of mastery of the exponential number through Discovery learning approach in learning of mathematic. Subject and source of research data is a total of 32 learners. Methods of data collection using observation, documentation, and testing. Analysis of data using a critical and comparative analysis. Indicators of success using the criteria limit minimal is 80 and the target class completeness 100%. Research procedure uses cycles. From the results of research and discussion is known that the data obtained from pre cycle until the second cycle, obtained achievement progress data obtained from pre cycle until the second cycle, obtained advances learning achievements of learners in mathematics with matter exponential number, the pre cycle average of 77 and the cycle I average of 83 and the second cycle by an average of 92. from this data, it seems clear that an increase in the average value of pre cycle to a first cycle of six figures (7.8%), from the first cycle to the second cycle occurs an increase of 9 numbers (10.8%), from the second cycle pasiklus to an increase of 15 points (19.5%). The highest value pre cycle stage by 86 and 90 as well as the first cycle of the second cycle of 98. It is clear that from the stage to the first cycle pre cycle an increase of 4 digits (4.7%), from the first cycle to the second cycle an increase of 8 digits ( 8.9%), and the second cycle of pre cycle to an increase of 12 points (14%). The lowest scores were obtained for 66 pre cycle stage and the first cycle of 72 and the second cycle of 88. thus, can be affirmed that the step of the first cycle pre cycle to an increase of 6 figures (9.1%), from the first cycle to the second cycle there is an increase amounting to 16 points (22.2%), and the second cycle of pre cycle to an increase of 22 points (33.3%). The percentage of mastery learning from pre cycle obtained by 34% and the first cycle was obtained by 66% and the second cycle of 100%. It seems clear that from the stage to the first cycle pre cycle an increase of 32%, from the first cycle to the second cycle an increase of 34%, and from the second cycle pre cycle to an increase of 66%. Thus, the learning achievements of learners in mathematics learning with the exponential number of pre cycle material to the second cycle brought a significant rise.